Single-joint eccentric knee extension training preferentially trains the rectus femoris within the quadriceps muscles - Maeo, S.; Shan, X.; Otsuka, S.; Kanehisa, H.; Kawakami, Y. (Translational Sports Medicine, 2018)
Eccentric contraction-induced quadriceps strains, particularly in the rectus femoris (RF), frequently occur in sports. By using MRI-based transverse relaxation time (T2) as an index of exercise-induced muscle edema, previous studies found pronounced damage in RF after an acute single-joint eccentric knee extension exercise. This study examined whether single-joint eccentric knee extension training would preferentially train RF, resulting in greater hypertrophy of RF than the other quadriceps muscles. Twelve males conducted work-matched single-joint isokinetic (180°/s) maximal eccentric contractions of the knee extensors in one leg (ECC-leg) and concentric in the other (CON-leg), six sets/session (3-5 sets in the initial 1-3 sessions), two sessions/wk for 10 weeks. Muscle volume of each quadriceps was measured pre- and post-training. T2 of each muscle was assessed weekly throughout the training period and pre- and post-training. Muscle volume significantly increased in all muscles in ECC-leg only, with a greater degree for RF (+7.3%) than the vasti (2.9%-3.7%). T2 did not change in all muscles throughout. These results suggest that RF can be preferentially trained by single-joint eccentric knee extension training. Cooperatively with the potential repeated bout effect (ie, protective effect) in eccentric exercise, this training modality would have positive implications for strain injury prevention of RF.